Brain alterations in autoimmune and pharmacological models of diabetes mellitus: focus on hypothalamic-pituitary-adrenocortical axis disturbances - Beauquis, Juan (2008)
Type 1 diabetes (T1D) is linked to an 'encephalopathy' explained by some features common to the aging process, degenerative and functional disorders of the central nervous system. In the present study we describe a manifest hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis in two different experimental mouse models of T1D including the pharmacological one induced by streptozotocin and the spontaneous NOD (nonobese diabetic mice). The high expression of hypothalamic hormones like oxytocin and vasopressin were part to this alteration, together with elevated adrenal glucocorticoids and prominent susceptibility to stress. In the hippocampus of diabetic animals a marked astrogliosis, often associated with neural damage, was present. Dentate gyrus neurogenesis was also affected by the disease: proliferation and differentiation measured by bromodeoxyuridine immunodetection were significantly reduced in both experimental models used. Several facts, including changes associated with chronic hyperglycemia, hyperstimulation of the HPA axis, increased levels of circulating glucocorticoids in combination with brain inflammation and low production of new neurons, contribute to emphasize the impact of diabetes on the central nervous system.